Analisis Perbandingan Kinerja Keuangan LPD (Lembaga Perkreditan Desa) di Daerah Pertanian dan Daerah Non Pertanian dengan Pendekatan Camel - PUTRA, I KOMANG YOGA PRAMANA; DEWI, RATNA KOMALA; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
C omparative A nalysis of F inancial P erformance of V illage C redit I nstitutions (LPD) in A gricultural and N on- A gricultural R egions with T he CAMEL A pproach Village Credit Institution (LPD) is a village-owned non-bank financial institution that carries out business activities in the village environment and for the village community. Regional differences affect the financial performance of LPD in each region so it is necessary to conduct an analysis of the financial performance of LPD in accordance with Bali Governor Regulation Number 44 of 2017 about Village Credit Institutions by using CAMEL analysis. This research aims to determine the financial performance of LPD Desa Adat Serampingan as an example of LPD in agricultural village and LPD Desa Adat Banjar Anyar as LPD in non-agricultural village and also to find out the financial performance comparison of the two LPDs. The data used are primary data in the form of supporting data, namely information about the profiles of each LPD and secondary data in the form of financial statements of each LPD. The type of data used is quantitative data. The results of this study is that LPD Desa Adat Serampingan as agricultural LPD areas and LPD Desa Adat Banjar Anyar as non-agricultural LPD earned a healthy predicate, which means they have good financial performance, but the financial performance of LPD Desa Adat Banjar Anyar is better than LPD Desa Adat Serampingan.